Kontrol Diri dan Kematangan Emosi Siswa - Adelia, Ela; Nur Budiono, Arifin (Universitas PGRI Kanjuruhan Malang, 2024)
Education at junior high school level has an important role in shaping students' character and emotional development. One aspect that can influence emotional maturity is self-control. The aim of this research is to determine the relationship between self-control and emotional maturity of class VIII students at SMPN 3. This type of research is quantitative research, this type of research is correlational. The subjects of this research were class VIII students of SMPN 3 TANGGUL for the 2023-2024 academic year. The instrument used was a self-control and emotional maturity questionnaire. Data were analyzed using product moment correlation techniques. The research results show a positive correlation between emotional maturity and self-control of 3.272505. Meanwhile, the r table with degrees of freedom (df 108-2 106) at a significance level of 0.05 obtained a t table value of 1.65936. which means the correlation in the research is significant.